Tourism development and the sense of place - Christou, Prokopis A.; Saveriades, Alexis; Farmaki, Anna (My University, 2018)
Destinations may follow a development process from birth to decline, or alternatively other paths (Hovinen, 2002; Butler, 2009), such as an “s-shaped” route (Moore & Whitehall, 2005). Nonetheless, they may go through a phase in which they may encounter certain (e.g. environmental) impacts (Plog, 2001; Zhong et al., 2011). The purpose of this study is to explore whether, and the extent of which, tourism development affects the “sense of a place”; The latter, offers a way to understand the relationship between individuals and the places they inhabit, recreate and manage (Mullendore et al., 2015). Understanding the deeper meanings of sense of place and its correlation with tourism activity, may equip destinations with the necessary knowledge in order to protect the identity, appeal and sense of their place. The study makes use of auto-ethnographic findings (Komppula & Gartner, 2013) in a specific region of Cyprus, which experienced intense tourism development. Particularly, it focuses on the physical aspect of the particular place, by examining the landscape changes within the region, as a result of touristic activity. The analysis of visual documentation (Scarles, 2010; Li et al., 2016) in the form of photographs derived from the setting, in comparison with archaic photographic evidence, assist in addressing the study’s aim. Preliminary findings indicate that tourism developmental processes, do affect the sense of a place. Though, rather unforeseen fieldwork findings reveal that specific sites within the destination have kept their “sense” untouched and unaffected throughout the centuries. Destination stakeholders are urged to refer to these sites to comprehend which precise elements and factors contributed to their preserved character and sense.
Keywords: Tourism Development; Destination